Germacrone Regulates HBXIP-Mediated Cell Cycle, Apoptosis and Promotes the Formation of Autophagosomes to Inhibit the Proliferation of Gastric Cancer Cells - Fang, Xing; Tan, TingFei; Gao, BeiBei; Zhao, YingLi; Liu, TingTing; Xia, Quan (Frontiers in Oncology, 2020)
Germacrone, a monocyclic sesquiterpene, exerts marked antitumor effects in a variety of cancers, including hepatocellular carcinoma, gastric cancer, and breast cancer. However, the mechanism underlying the effects of germacrone on gastric cancer remains unclear. In this study, we show that germacrone inhibited gastric cancer cell proliferation in a dose-dependent manner, and induced G0/G1-phase cell cycle arrest and apoptosis in these cells. Moreover, germacrone increased the expression of LC3II/LC3I. And LC3II/LC3I was significant increased after germacrone treatment compared with germacrone and bafilomycin A1 (Baf A1) treatment, which suggested germacrone promoted the formation of autophagosomes. Proteomic analysis was then used to identify molecular targets of germacrone in gastric cancer. A total of 596 proteins were screened, and the top hit was identified as late endosomal/lysosomal adaptor and MAPK and MTOR activator 5 (LAMTOR5, also named HBXIP). Overexpression of HBXIP delayed the germacrone-induced cell cycle arrest, induction of apoptosis, and inhibition of autophagy. Combined, our results indicate that germacrone suppresses gastric cancer cell proliferation by inhibiting HBXIP, and this process is related to G0/G1-phase arrest and apoptosis.